Semantic-cognitive structure of social-philosophical discourse of the end of xixth - the beginning of the xxth century - Olga Sergeevna, Fisenko (2019)
The article discusses the features of the Russian religious and philosophical discourse of the late XIXth – early XXth centuries. The subject of study is the archaic meanings of socio-philosophical discourse concepts and their semantic transformations, as well as new meanings that appeared in the late XIXth – early XXth centuries. It is proved that the “EVENT” concept, which includes the composite components “Kingdom”, “Emperor”, “Russians” and “literature”, is structurally-forming.